Pengaruh Motivasi, Lingkungan, Disiplin, dan Keadilan Organisasi terhadap Kinerja Karyawan - Ayu Nur, Luthfi; Kharismasyah, Alfato Yusnar; Astuti, Herni Justiana; Widhiandono, Hengky (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2023)
This study aims to analyze the effect of work motivation, work environment, work discipline, and organizational justice on employee performance at Laksana Baru Swalayan Majenang. The research method used is a survey using a questionnaire as a data collection instrument. The data obtained were analyzed using PLS. The results showed that work motivation, work environment, work discipline, and organizational justice had a significant positive effect on employee performance. Work motivation and work environment have a strong positive influence on employee performance, while work discipline and organizational justice have a moderate positive influence on employee performance. So, Laksana Baru Swalayan Majenang needs to focus on increasing employee motivation and work environment, as well as improving work discipline and organizational justice to improve employee performance. This research is expected to contribute to the development of human resource management in Indonesia.